Transient effects of glyphosate on microbial parameters in soil microcosms - Viviane Sobucki (Universidade Federal Rural da Amazônia (UFRA), 2021)
Microbial parameters were determined during 28 days in soil microcosms spiked with glyphosate at the recommended dose (RD) and 10-fold RD (10X), as well in non-contaminated controls (CM). Soil respiration rates were stimulated by glyphosate after 1-3 days. Cumulative soil respiration in 10X was 52% and 32% higher than CM and RD, respectively. Total hydrolytic activity was similar between treatments during 0-14 days; lower activities were measured in CM/RD after 21 days and in RD after 28 days. Lower soil dehydrogenase activity was detected in contaminated soils after 7 and 21 days, but activities were comparable to CM at day 28. Total heterotrophic bacteria were higher in CM after 14 days; after 28 days, higher counts were observed in CM/10X microcosms. Microbial biomass carbon (MBC) at day 1 was negatively affected by 10X; however, it returned to CM/RD values at day 28. The metabolic quotient (qCO2) indicated a higher microbial stress in 10X at day 1; after 28 days, values were similar between treatments. In summary, the microbial indicators were changed in a transitory way by glyphosate. Therefore, no short-term detrimental effects are expected in terms of microbial numbers and activities. Studies to assess the diversity and structure of the soil bacterial community in response to glyphosate application are indicated.